The Effect of External Auditor Quality, Arrogance, and Female CFO on Financial Statement Fraud with Audit Committee Financial Expertise as a Moderating Variable (Study of Non-Financial Sector Companies Listed on the Indonesia Stock Exchange for the Period - Berlika Sharla Martiza; Hasni Yusrianti; Tertiarto Wahyudi (International Journal Multidisciplinary Science, 2026)
This study aims to examine and analyze the effect of external auditor quality, arrogance, and female CFO on financial statement fraud, with audit committee financial expertise as a moderating variable. This study used a quantitative approach with secondary data from non-financial sector companies listed on the Indonesia Stock Exchange for the period 2022–2024. The study sample consisted of 408 companies with a total of 1,224 observations. Data analysis was performed using panel data regression with Eviews version 12 software. The results show that external auditor quality has a positive and significant effect on financial statement fraud. Arrogance has no significant effect on financial statement fraud. Female CFO has a negative and significant effect on financial statement fraud. Audit committee financial expertise is not proven to moderate the relationship between external auditor quality and arrogance on financial statement fraud. However, audit committee financial expertise has been shown to moderate the relationship between female CFOs and financial statement fraud.